Waiting time among diabetic patients in a local health clinic - Shalihin, Mohd Shaiful Ehsan; Zolcefli, Nur Atiqah; Mohd Ismail, Nurul Syahirah; Zuhari, Zur Ain (IIUM Press, 2019)
Waiting time among diabetic patients is becoming an important issue considering the increasing number of this population requiring to follow up in primary care clinic. Diabetic patients have multiple stations to be visited, causing them to have a longer waiting time compared to other patients. Their dissatisfaction should be investigated for further improvement, and this should be proved. This study aims to measure the waiting and consultation time of diabetic patients attending a non-communicable disease clinic session in Klinik Kesihatan Seremban. A cross-sectional study was done among 190 diabetic patients in which their waiting and consultation time had been recorded. SPSS version 23 is used for statistical analysis. Most of the patients were age 64 (6.3%), female (63.7%) and Indian ethnicity (44.7%). 78.4% of them were also hypertensive, and 50.5% of them had dyslipidaemia. The majority had three concomitant chronic diseases (46.8%). Maximum waiting time recorded was 104 minutes, with a minimum waiting time of 2 minutes. Average waiting time was 32.73+24.37 minutes. Maximum consultation time was 45 minutes, with an average time of 9.61+6.27 minutes. There is no significant association between waiting or consultation time with age, gender, races and number of concomitant illness. This study showed that the clinic has an acceptable duration of waiting and consultation time with an average of less than 45 minutes which is fulfilling the requirements set by the Ministry of Health. The misconception of unacceptable long waiting time experienced by diabetic patients and chronic disease should be corrected. This study proved that waiting and consultation time is not determined by the demographics of the patient and disease only in which patient and public education on the acceptable waiting time should be implemented regularly.